ANALYSIS OF INFLUENCING FACTORS STREET VENDOR INCOME IN NEW SUB-DISTRICT BAOLAN TOLITOLI REGENCY (Case Study of Arang Tampurung Business): ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG JALANAN DI KECAMATAN BARU BAOLAN TOLITOLI KABUPATEN (Studi Kasus Usaha Arang Tampurung) - Ismail Ismail; Hairuddin Hairuddin (STIE MUJAHIDIN TOLITOLI, 2024)
This study aims to analyze the influence of business capital, working hours, business duration, and education level. The study is a quantitative research with primary data from the results of the questionnaire on a sample of street vendors in the New Village.The number of respondents to street vendors in the new Village is 53.The data from the questionnaire is processed using a linear probability model and processed using SPSS software. The results of the test were obtained on the variable